Development of Web-Based Student Registration Information System with Rapid Application Development Approach - Arif Tri Widiyatmoko; Agung Nugroho; Wiyanto Wiyanto (Information Technology and Science (ITScience), 2024)
The management of student data and the student registration process is an important aspect in the world of education. In the digital era, the use of information technology is crucial to maintain the quality and efficiency of education. Therefore, the development of a web-based student registration information system with a Rapid Application Development (RAD) approach is an efficient and effective solution. This research proposes the development of a web-based student enrolment information system with a RAD approach to improve efficiency, accessibility of student data, and the ability to adapt the system to continuous change. The RAD method consists of requirements planning stages, RAD design workshops, and implementation. The test results of the application show that this application is worth using and meets the expected standards. Thus, the development of a web-based student registration information system with the RAD approach is expected to provide innovative and efficient solutions in overcoming student data management problems and the student registration process